1994
DOI: 10.1063/1.111247
|View full text |Cite
|
Sign up to set email alerts
|

Band lineup at an organic-inorganic semiconductor heterointerface: perylenetetracarboxylic dianhydride/GaAs(100)

Abstract: We present a photoemission study of the electronic properties of an interface between the organic semiconductor; 3, 4, 9,10 perylenetetracarboxylic dianhydride (PTCDA) and n-type GaAs(100). We examine the evolution of the interface electron distribution as a function of PTCDA overlayer thickness. The highest occupied molecular orbital level of PTCDA is measured at 0.7±0.1 eV below the GaAs valence band maximum. The PTCDA ionization potential is measured at 6.4±0.15 eV. The discrepancy between the band alignmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
42
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 15 publications
2
42
0
Order By: Relevance
“…the energy gap relevant for charge carrier transport was measured with optical absorption spectroscopy, as is common for inorganic semiconductors (IOSCs) [3]- [5]. Later, Kahn and co-workers [6] and Seki and co-workers [7] pioneered the approach of using photoelectron spectroscopy (PES) with UV-and x-ray excitation (UPS and XPS, respectively) and inverse photoelectron spectroscopy (IPS).…”
Section: Definition Of the Transport Level For Organic Semiconductorsmentioning
confidence: 99%
“…the energy gap relevant for charge carrier transport was measured with optical absorption spectroscopy, as is common for inorganic semiconductors (IOSCs) [3]- [5]. Later, Kahn and co-workers [6] and Seki and co-workers [7] pioneered the approach of using photoelectron spectroscopy (PES) with UV-and x-ray excitation (UPS and XPS, respectively) and inverse photoelectron spectroscopy (IPS).…”
Section: Definition Of the Transport Level For Organic Semiconductorsmentioning
confidence: 99%
“…On the other hand, it is clearly seen that feature C at $8.9 eV appears only at a larger value of . Hirose et al (1994Hirose et al ( , 1996 ascribed the photoemission peak, which corresponds to the present feature C, to the % 3 state. Band A originates from the HOMO of % character and, therefore, feature C should not originate from the valence state of % character since the difference in these dependencies is re¯ected in the wavefunctions of the initial states.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was reported that thin ®lms of PTCDA provide new band-gap states due to the reaction at the interface between the ®lm and the substrate or over-layer materials such as GaAs, In, Al, Ti and Sn (Hirose et al, 1994(Hirose et al, , 1996. The reaction between the molecule and metal atoms was considered to occur at the C O groups in the molecule (Hirose et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…1͑a͒, has recently gained much interest as a promising component for organic electroluminescence devices. It was reported that for a thin film of PTCDA a new state in the PTCDA band gap appears due to the interaction between the organic film and the inorganic substrate or overlayer materials such as GaAs, 2 In, Al, Ti, and Sn. 3 This result is very important because the new state is located very close to the Fermi level, and therefore it is expected that it plays an important role in organic device properties.…”
Section: Introductionmentioning
confidence: 99%